Social perception about birth as a demographic phenomenon - Sandu, Mihaela Luminita; Rus, Mihaela; Pruteanu, Lavinia (Technium Social Sciences Journal, 2021)
Birth has become a phenomenon of increasing concern. The population of Romania has decreased and is constantly decreasing, the downward evolution is not surprising, all the information on the natural and migratory movement after 1989 define a well-installed demographic decline. Romania's demographic decline is gaining new dimensions and amplifying the deterioration of the country's demographic situation. What is less known and evaluated at the true value is the depth of the deterioration of the age structure of the population in the context of the demographic decline and the implications of this deterioration from the perspective of the possible recovery of the demographic state of the country. The present demographic evolutions, respectively the characteristics of the components that have produced and are still producing these evolutions, foreshadow a strongly negative image regarding the population of Romania in the next decades, if by public policies the birth ratio will not be stimulated.